Missing Screw as a Rare Complication of Anterior Cervical Instrumentation - Yusuf Kurtuluş Duransoy; Mesut Mete; Baha Zengel; Mehmet Selçukı (Case Reports in Orthopedics)
Although anterior cervical arthrodesis is an effective procedure for the treatment of cervical disorders, the method has some complications. Here, we describe this rare complication of cervical instrumentation with a literature review. A 23-year-old male patient was operated for a C6-C7 dislocation. At postoperative month 10, he presented with hemoptysis and dysphagia. Cervical roentgenograms showed anterior migrations of one broken screw and a plate-locking screw at the C6 corpus. One screw was missing. We concluded that the missing screw had perforated the esophagus and had been eliminated spontaneously through the gastrointestinal tract. No screw should migrate. Even loose screws should be noted in follow-up X-ray studies. If such findings are detected, a second operation for revision should be considered as soon as possible to prevent potentially fatal complications.